Application of MCTS in Tsumego of Computer Go - Fang Wang; Ying Peng (Institute of Advanced Engineering and Science, 2013)
The Tsumego problem in Go was a basic and essential problem to be overcome in implementing a computer Go program. This paper proposed a reality of Monte-Carlo tree search in Tsumego of computer Go which using Monte-Carlo evaluation as an alternative for a positional evaluation function. The advantage of this technique was that it requires few domain knowledge or expert input. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1991